Alterations in microRNA expression in the tissues of silver carp (Hypophthalmichthys molitrix) following microcystin-LR exposure. (15th March 2017) - Feng, Yiyi; Ma, Junguo; Xiang, Ruichen; Li, Xiaoyu
Abstract: In the field of toxicology, the relationship between microRNAs (miRNAs) and microcystin-LR (MC-LR) toxicity in fish is still poorly understood. In the present study, we used quantitative real-time PCR (qPCR) to examine the expression of 7 miRNAs (let-7b, miR-21, miR-122, miR-27b, miR-148, miR-125a, and miR-143) that play regulatory roles in biological processes such as signal transduction, apoptosis, cell cycle, and fatty acid metabolism. Expression patterns were assessed in the liver, spleen, and kidney of silver carp following 8, 24, and 48 h of exposure to MC-LR via intraperitoneal injection (50 or 200 μg/kg of body weight). The results of qPCR analysis showed that the expression of the 7 miRNAs was either upregulated or downregulated in response to MC-LR exposure. These results indicate that acute MC-LR exposure altered miRNAs expression profiles in the liver, spleen, and kidney of silver carp, suggesting that miRNAs may be involved in MC-LR toxicity. Highlights: Seven miRNAs expression in the tissues of MC-LR-treated silver carp was determined. miRNAs expression was altered in response to MC-LR exposure. Our results suggest that microRNAs may be involved in MC-LR toxicity.